A multi-sensor-based distributed real-time measurement system for glacier deformation - Dong, Han-chuan; Liu, Shuang; Pang, Li-li; Tao, Zhi-gang; Fang, Li-de; Zhang, Zhong-hua; Li, Xiao-ting (Journal of mountain science, 2023)
Glacier disasters occur frequently in alpine regions around the world, but the current conventional geological disaster measurement technology cannot be directly used for glacier disaster measurement. Hence, in this study, a distributed multi-sensor measurement system for glacier deformation was established by integrating piezoelectric sensing, coded sensing, attitude sensing technology and wireless communication technology. The traditional Modbus protocol was optimized to solve the problem of data identification confusion of different acquisition nodes. Through indoor wireless transmission, adaptive performance analysis, error measurement experiment and landslide simulation experiment, the performance of the measurement system was analyzed and evaluated. Using unmanned aerial vehicle technology, the reliability and effectiveness of the measurement system were verified on the site of Galongla glacier in southeastern Tibet, China. The results show that the mean absolute percentage errors were only 1.13% and 2.09% for the displacement and temperature, respectively. The distributed glacier deformation real-time measurement system provides a new means for the assessment of the development process of glacier disasters and disaster prevention and mitigation.